CONSUMER’S PERCEPTION TOWARDS NEUROMARKETING IN INDIA WITH SPECIAL REFERENCE TO KANO MODEL - Kumar, Harit; Mathur, Neha; Jauhari, Sangeeta (International Journal of Research -GRANTHAALAYAH, 2017)
This paper presents how consumer’s perception towards neuromarketing can be analyzed by using Kano model and discusses the potential benefits that can be achieved by applying this approach to skis the application of neuromarketing. Neuromarketing investigates important information that commonly consumer purchase decisions take place at a mental, emotional and instinctive level; those take place in the subconscious brain that is under the levels of controlled awareness. Due to this striking motive, the perception technologists of the market are extremely keen to study the techniques of successful handling of the subconscious brain actions. The major reason is to encourage the preferred response in person’s perception as intensely as possible. This article with the application of Kano Model examines the impact of application of neuroscience techniques on marketing practices as these communicate to the exercise of individual free will. This study centers to investigate the consumer’s perception towards neuromarketing by Kano questionnaire; includes questions involving consumers’ awareness, consent, and understanding to what may be viewed as foray of their privacy rights.